A multi-institutional outbreak of New Delhi metallo-β-lactamase–producing Escherichia coli with subsequent acquisition of the Klebsiella pneumoniae carbapenemase gene. (29th September 2021) - Solter, Ester; Kwong, Jason C.; Walton, Aaron; Sherry, Norelle; Howden, Benjamin P.; Grayson, M. Lindsay; Schwartz, David; Temkin, Elizabeth; Frenk, Sammy; Carmeli, Yehuda; Schwaber, Mitchell J.
Abstract: We characterized 57 isolates from a 2-phase clonal outbreak of New Delhi metallo-β-lactamase–producing Eschericha coli, involving 9 Israeli hospitals; all but 1 isolate belonged to sequence-type (ST) 410. Most isolates in the second phase harbored bla KPC-2 in addition to bla NDM-5 . Genetic sequencing revealed most dual-carbapenemase–producing isolates to be monophyletically derived from a common ancestor.